Name: Majeedah Who is asking: Student Level of the question: Secondary Question: I'm upgrading thru correspondence and haven't been in school for a long while, so I have no class or teacher to explain the basics to me. I have a couple of questions: The problem is this: f(x) = x2 - 2, Find the expression. Q f(-x) A x2 - 2 Why is the answer not -x2 - 2? A relation f, is given by f(x) = x - 2/x. Find the expression. Q 2/f(3) A 6 How do you get the answer. Majeedah, What this means is you need to substitute "-x" for all values of "x" in the expression: f(-x) = (-x)2 - 2 but since (-x)2 = (-x) (-x) and the product of two negative numbers is positive, (-x)2 = x2. By convention, when we simplify this expression we drop the minus sign because it is simpler to write x2 than (-x)2. Hence f(-x) = x2 - 2. Writing -x2 - 2 is not the same as (-x)2 -2 because the order of operations (look up "BEDMAS" in our search form for more information on this) says that the x2 must be evaluated before the minus. For example, if x is 2, then -22 - 2 = - 2 2 - 2 = -4 - 2 = -6, but (-2)2 - 2 = (-2) (-2) - 2 = 4 - 2 = 2. Replace x with 3 to find f(3): f(3) = 3 - 2/3. Put that under 2 to find 2/f(3): 2/f(c) = 2 / (3- 2/3) Now you simplify the left-hand side to get the answer: 2 / (3 - 2/3) = 2 / (7/3) = 2 (3/7) = 6/7 Clearly the answer is not 6, but 6/7. I'm guessing that you forgot some parentheses. If f(x) = (x-2) / x then f(3) = (3-2) / 3 = 1/3 and so 2 / f(3) = 2 / (1/3) = 2 (3/1) = 6.   Hope this helps, Stephen La Rocque.